Influence of severity of type and timing of retrospectively reported childhood maltreatment on female amygdala and hippocampal volume - Herzog, Julia; Thome, Janine; Demirakça, Traute; Koppe, Georgia; Ende, Gabriele; Lis, Stefanie; Rausch, Sophie; Priebe, Kathlen; Müller-Engelmann, Meike; Steil, Regina; Bohus, Martin; Schmahl, Christian (Scientific reports, 2020)
Deleterious effects of adverse childhood experiences (ACE) on human brain volume are widely reported. First evidence points to differential effects of ACE on brain volume in terms of timing of ACE. Upcoming studies additionally point towards the impact of different types (i.e., neglect and abuse) of ACE in terms of timing. The current study aimed to investigate the correlation between retrospectively reported severity of type (i.e., the extent to which subjects were exposed to abuse and/or neglect, respectively) and timing of ACE on female brain volume in a sample of prolonged traumatized subjects. A female sample with ACE (N = 68) underwent structural magnetic resonance imaging and a structured interview exploring the severity of ACE from age 3 up to 17 using the “Maltreatment and Abuse Chronology of Exposure” (MACE). Random forest regression with conditional interference trees was applied to assess the impact of ACE severity as well as the severity of ACE type, (i.e. to what extent individuals were exposed to neglect and/or abuse) at certain ages on pre-defined regions of interest such as the amygdala, hippocampus, and anterior cingulate (ACC) volume. Analyses revealed differential type and timing-specific effects of ACE on stress sensitive brain structures: Amygdala and hippocampal volume were affected by ACE severity during a period covering preadolescence and early adolescence. Crucially, this effect was driven by the severity of neglect.
Gesehen am 10.03.2020